Peritonitis in patients on peritoneal dialysis: a 12-year experience from a large medical center in Bursa - Gül, Bülent (The European Research Journal, 2024)
Objectives: Despite all technical advances, Peritonitis remains the most important peritoneal dialysis (PD) complication. Peritonitis causes complications such as additional hospitalization, technical failure, peritoneal membrane damage, consequent transition to hemodialysis, and death in this patient group. Early diagnosis, isolation of the causative pathogen with appropriate methods as soon as possible, and determination of antibiotic susceptibilities play a crucial role in solving the problem of treating peritonitis in PD. This study evaluated the frequency of peritonitis, culture positivity rate, and prognosis in peritoneal dialysis patients in our unit for 12 years. Methods: A total of 171 patients (80 F, 91 M; mean age: 51.9±15.3 year; mean PD duration 36.5±36.4 months) who were followed up in our department between January 2009 and July 2021 were included in the study. Patient records were retrospectively analyzed. Results: Peritonitis never occurred in 105 of the 171 patients included in the study. Of the remaining 66 patients, 43 had one peritonitis attack, and 23 had more than two. The mean peritonitis rate was 1.68±1.36. One hundred eleven episodes of peritonitis were detected in 66 of the patients. Bacterial growth was observed in 63.06% of the culture samples obtained from the 93 peritonitis episodes. The peritoneal catheter was withdrawn in 14 (21.21%) cases. Conclusion: In our unit, the rate of culture positivity was 63.06%, and the peritonitis attack rate was 0.017 per patient-month and 0.211 per patient-year over a period of twelve years, with a mean of 57.1 patient months of peritonitis.